The Development of Side Scroller Application: The Legend of Merong Maha Wangsa - Nik Bahrudin, Nik Aiman Najmi; Murli, Norhanifah (Applied Information Technology And Computer Science, 2025)
From pixelated pioneers like Mario to modern marvels like Celeste, side scrollers captivate us with their simple controls, pixel-perfect platforming, and captivating journeys across stunning 2D worlds. This timeless genre, spanning playful platformers to gritty metroidvanias, offers a spectrum of stories, challenges, and discoveries, all unfolding beautifully within the confines of a horizontal scroll. The purpose of the project is to take on a journey through history and culture. In this game, the player will travel to a different time period and place, and experience historical events and cultures from all over the world (linked to the Merong Maha Wangsa’s story) all while collecting their golds. The aim of the project is create a game where the player can both have fun and learn at the same time. The game is made available on Windows and platform. The software used is Godot while using Agile methodology. The target Audience will be those from age 12 to 75. This application is expected to help those who are interested in learning about the history of Merong Maha Wangsa.